2016
DOI: 10.1095/biolreprod.116.142273
|View full text |Cite
|
Sign up to set email alerts
|

Placental Hypoxia During Early Pregnancy Causes Maternal Hypertension and Placental Insufficiency in the Hypoxic Guinea Pig Model

Abstract: Chronic placental hypoxia is one of the root causes of placental insufficiencies that result in pre-eclampsia and maternal hypertension. Chronic hypoxia causes disruption of trophoblast (TB) development, invasion into maternal decidua, and remodeling of maternal spiral arteries. The pregnant guinea pig shares several characteristics with humans such as hemomonochorial placenta, villous subplacenta, deep TB invasion, and remodeling of maternal arteries, and is an ideal animal model to study placental developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 52 publications
4
65
0
1
Order By: Relevance
“…We speculate that our cyclic hypoxic profile (12% FnormalIO2) was not severe enough to prevent proper trophoblast invasion, as results in a pig model of hypoxia demonstrated that while a hypoxic exposure of 10.2% FnormalIO2 impaired trophoblast invasion and placental damage, there was little or no effect when FnormalIO2 was 16% or 12% during pregnancy (Thompson et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…We speculate that our cyclic hypoxic profile (12% FnormalIO2) was not severe enough to prevent proper trophoblast invasion, as results in a pig model of hypoxia demonstrated that while a hypoxic exposure of 10.2% FnormalIO2 impaired trophoblast invasion and placental damage, there was little or no effect when FnormalIO2 was 16% or 12% during pregnancy (Thompson et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Humans as well as animals can be exposed to hypobaric (HH) or normobaric hypoxia (NH) in order to study wide variety of diseases, including pulmonary hypertension (20), reoxygenation injury (21), pre-eclampsia (22), hypoxic insult of the brain (23), and diabetic retinopathy (24). While HH, which physically resembles a high-altitude environment, is induced by decreasing atmospheric pressure under 101 325 Pa (1 atm, 760 mm hg) typically in a tightly sealed hypobaric chamber (25), NH exposure is based on the reduction of the partial pressure of oxygen (pO 2 ) at normal atmospheric pressure, which typically occurs through the administration of nitrogen to a face mask (26), hypoxic tent (27), or environmental chamber (22,23).…”
Section: In Vivo Models Of Hypoxiamentioning
confidence: 99%
“…Animal surgical procedures and sampling. C. cobaya has treatmented for 10 days prepartum, then postpartum first day was performed dislocation using overdose anesthesia (Thompson et al, 2016) and was followed by rapid surgery to remove the liver organs. Liver organs was stored in 10% formalin solution to histopathology and toxicity testing (Thompson et al, 2016;Samik and Safitri, 2017).…”
Section: Experimental Designmentioning
confidence: 99%
“…The tissue sheets were immersed in eosin hematoxylin for 10 minutes and rinsed with running water (Cakir et al, 2015). Then, 96% alcohol (I), alcohol 96% (II), absolute alcohol (III), absolute alcohol (Nithianantham et al, 2011) was washed for 3 min followed by xylol (Thompson et al, 2016;Cakir et al, 2015;Pradana et al, 2016).…”
Section: Experimental Designmentioning
confidence: 99%